(untitled) (Altre Modernità, 2012)
The present paper focuses on the presentation of a transdisciplinar methodology of analysis of the ‘vertical connectivity’ (human society-landscape interaction) that is being developed with the collaboration of the different teams participating in the study for the elaboration of the Natural Resources Planning for the proposal of creation of a National Park in the island of Fuerteventura. The proceeding tries to es¬ta¬blish by a combination of quantitative and qualitative techniques the formal rela¬tion between cartesian landscape and socioeconomy with the aim of explaining the im¬pli¬cations of the actual socioeconomic changes in the maintenance of landscape. Fuerteventura’s economy is heavily dependent on tourism, and precisely because of that, it is having rapid socioeconomic changes. The proceeding has not been totally realized yet in this context, but will be exposed a part of the results obtained so far on the analysis of the socioeconomic characteristics of Fuerteventura.